To solve the equation \(-\frac{3}{5}x = \frac{2}{5}\) using inverse operations, we can follow these steps:
- Isolate \(x\): To isolate \(x\), we need to eliminate the coefficient \(-\frac{3}{5}\) by multiplying both sides of the equation by the reciprocal of \(-\frac{3}{5}\), which is \(-\frac{5}{3}\).
\[ x = \frac{2}{5} \cdot -\frac{5}{3} \]
- Multiply the fractions:
\[ x = \frac{2 \cdot -5}{5 \cdot 3} = \frac{-10}{15} \]
- Simplify:
\[ x = -\frac{10}{15} = -\frac{2}{3} \]
Now, we need to check which option matches this result. The solution \(x = -\frac{2}{3}\) matches:
- Option C: \(-2\frac{3}{2}\) which is actually \(-2\) and needs translation.
To summarize, the solution to the equation is:
\[ x = -\frac{2}{3} \]
Thus the correct answer based on the available options is:
C: \(-2\frac{3}{2}\) is \(-\frac{2}{3}\) directly solving yielded a value that is unaccounted. Please clarify or check all options presented for match. If only this option exists, it is the nearest equivalence but confirmed error in formatting in analysis as described.